Wasting the Future: The Technological Sublime, Communications Technologies, and E-waste - Sabine LeBel (communication +1, 2012)
Literally speaking, e-waste is the future of communications. E-waste is the fastest growing waste stream in the world, much of it communications technologies from cell phones to laptops, televisions to peripherals. As a result of policies of planned obsolescence working computers, cell phones, and tablets are routinely trashed. One of the most powerful and enduring discourses associated with emerging technologies is the technological sublime, in which technology is seen as intellectually, emotionally, or spiritually transcendent. It comprises a contradictory impulse that elevates technology with an almost religious fervor, while simultaneously overlooking some of the consequences of industrialism, as well as ignoring the necessity of social, economic, and governmental infrastructures necessary to the implementation and development of new technologies. The idea that a new technology will not pollute or harm the environment is a persistent, though often quickly passed over, theme in the technological sublime, echoed in discourses about emerging technologies such as the silicon chip, the internet, and other ICTs. In this paper, I make connections between the discourse of newness, the practice of planned obsolescence, and the mountains of trashed components and devices globally. Considering the global context demonstrates the realities of the penetration of ICTs and their enduring pollution and negative implications for the health of humans and nonhumans, including plants, animals, waterways, soil, air and so on. I use the discourse of the technological sublime to open up and consider the future of communications, to argue that this discourse not only stays with us but also contains within it two important and related components, the promise of ecological harmony and a future orientation. I argue that these lingering elements keep us from considering the real future of communications – e-waste – and that, as communications scholars, we must also engage with waste management literature and practices if we take the future of communications seriously. Note: Download statistics restarted from zero effective January 1, 2024. Please follow this link to see cumulative download statistics from our previous publishing platform: CPO Download Statistics 2012 - 2023
Keywords: e-waste; technological sublime; future; communication technologies